Structural and Chemical Profiles of Myrcia splendens (Myrtaceae) Leaves Under the Influence of the Galling Nexothrips sp. (Thysanoptera) - Jorge, Nina Castro; Souza-Silva, Érica A.; Alvarenga, Danielle Ramos; Saboia, Giovanni; Soares, Geraldo Luiz Gonçalves; Zini, Cláudia Alcaraz; Cavalleri, Adriano; Isaias, Rosy Mary Santos (Frontiers in Plant Science, 2018)
Thysanoptera-induced galls commonly culminate in simple folding or rolling leaf gall morphotypes. Most of these galls are induced by members of the suborder Tubulifera, with only a few species of the suborder Terebrantia being reported as gall inducers. The Terebrantia, as most of the gall inducers, manipulates the host plant cellular communication system, and induces anatomical and biochemical changes in its host plant. In an effort to keep its homeostasis, the host plant reacts to the stimuli of the galling insect and triggers chemical signaling processes. In contrast to free-living herbivores, the signaling processes involving galling herbivores and their host plants are practically unknown. Current investigation was performed into two steps: first, we set the structural profile of non-galled and galled leaves, and looked forward to find potential alterations due to gall induction by an undescribed species of Nexothrips (suborder Terebrantia) on Myrcia splendens. Once oil glands had been altered in size and number, the second step was the investigation of the chemical profile of three tissue samples: (1) non-galled leaves of a control individual, (2) non-galled leaves of galled plants, and (3) galls. This third sample was divided into two groups: (3.1) galls from which the inducing thrips were manually removed and (3.2) galls macerated with the inducing thrips inside. The chemical profile was performed by gas chromatography/ mass spectrometric detector after headspace solid-phase extraction. The galling activity of the Nexothrips sp. on M. splendens culminates in mesophyll compactness interspersed to diminutive hypersensitive spots, development of air cavities, and the increase in size and number of the secretory glands. Seventy-two compounds were completely identified in the volatile profile of the three samples, from which, sesquiterpenes and aldehydes, pertaining to the “green leaf volatile” (GLVs) class, are the most abundant. The rare event of gall induction by a Terebrantia revealed discrete alterations toward leaf rolling, and indicated quantitative differences related to the plant bioactivity manipulated by the galling thrips. Also, the content of methyl salicylate has varied and has been considered a potential biomarker of plant resistance stimulated as a long-distance effect on M.splendens individuals.